2010
DOI: 10.1128/mcb.01527-09
|View full text |Cite
|
Sign up to set email alerts
|

Repression of IP-10 by Interactions between Histone Deacetylation and Hypermethylation in Idiopathic Pulmonary Fibrosis

Abstract: Targeted repression of a subset of key genes involved in tissue remodeling is a cardinal feature of idiopathic pulmonary fibrosis (IPF). The mechanism is unclear but is potentially important in disease pathogenesis and therapeutic targeting. We have previously reported that defective histone acetylation is responsible for the repression of the antifibrotic cyclooxygenase-2 gene. Here we extended our study to the repression of another antifibrotic gene, the potent angiostatic chemokine gamma interferon (IFN-␥)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
69
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 50 publications
17
69
0
1
Order By: Relevance
“…Epigenetic regulation via miRNA has recently been extended to the altered expression of the DNA methylase DNMT-1 in IPF [216]. In accordance with these data, there is also evidence for altered DNA methylation in IPF lungs: epigenome analysis revealed globally altered methylation patterns of hundreds of CpG islands, but also of specific promoters of genes implicated in lung fibrosis, which correlated with altered expression of the respective genes [217][218][219][220][221]. In addition to DNA methylation, epigenetic histone modifications, in particular those mediated by HDACs, may contribute to lung fibrosis, as they were shown to regulate expression of single target genes of pulmonary fibrosis [220,222].…”
Section: Epigenetic Alterationssupporting
confidence: 55%
“…Epigenetic regulation via miRNA has recently been extended to the altered expression of the DNA methylase DNMT-1 in IPF [216]. In accordance with these data, there is also evidence for altered DNA methylation in IPF lungs: epigenome analysis revealed globally altered methylation patterns of hundreds of CpG islands, but also of specific promoters of genes implicated in lung fibrosis, which correlated with altered expression of the respective genes [217][218][219][220][221]. In addition to DNA methylation, epigenetic histone modifications, in particular those mediated by HDACs, may contribute to lung fibrosis, as they were shown to regulate expression of single target genes of pulmonary fibrosis [220,222].…”
Section: Epigenetic Alterationssupporting
confidence: 55%
“…These data are supported by data from human IPF tissues in which fibroblasts cultured from IPF samples have decreased levels of CXCL10 compared with non-IPF tissues because of epigenetic dysregulation. 45 Our own in silico analysis of the public Gene Expression Omnibus database (GDS1252) found that the genes for TCRg, TCRd, and CXCL10 are all expressed in the tissues of patients with IPF. However, these data do not offer any insight into the functionality of ␥␦ T cells and CXCL10 in humans.…”
Section: Discussionmentioning
confidence: 99%
“…To systematically screen for the epigenetic effects on CLDN14 gene expression, we treated the primary cultures of mouse TALH cells (freshly isolated from the C57BL/6 mice described before) 9,10 in vitro for 16 hours with the DNA methyltransferase inhibitor 5-Aza-29-deoxycytidine, the histone-lysine methyltransferase inhibitor BIX 01294, 24 the histone demethylase inhibitor tranylcypromine, 25 and the HDAC inhibitors trichostatin A (TsA) and suberanilohydroxamic acid 26 (SAHA; approved by the Food and Drug Administration as Vorinostat). 5-Aza-29-deoxycytidine, BIX 01294, and tranylcypromine were without significant effects on claudin-14 mRNA levels (Supplemental Figure 1).…”
Section: An Epigenetic Program Regulates the Mir-cldn14 Axis In The Kmentioning
confidence: 99%